DETERMINATION OF THE DIRECTION OF HOT FLUID FLOW IN CANGAR AREA, ARJUNO-WELIRANG VOLCANO COMPLEX, EAST JAVA USING SELF POTENTIAL METHOD - Dafiqiy Ya'lu Ulin Nuha; Sukir Maryanto; Didik Rahardi Santoso (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2017)
Research with self potential method has been done in Cangar area of Arjuno-Welirang volcano complex, East Java. The purpose of this study was determined the direction of hot fluid flow.  This hot fluid forms a geothermal manifestation of hot springs. Data acquisition has been done using fixed electrode configuration with interval 5 meters in 5 lines. In this configuration there are two porous pot electrodes, one of them set in fixed station and the other as mobile station. Based on the potential distribution value of the isopotential map, the lowest potential value about -54,5 mV and the highest value about 89,4 mV, so that in Cangar area can predicted the direction of hot fluid flow from southeast to northwest. Based on the results of this research in the direction of hot fluid flow can provide information about hydrothermal system in Cangar area for study of geothermal potential of Arjuno-Welirang Volcano complex, East Java